Uji Praktikalitas E-Modul Pembelajaran Project Based Learning Menggunakan Sigil Pada Mata Pelajaran Dasar-Dasar Kejuruan Siswa Kelas X Pengembangan Perangkat Lunak dan GIM (PPLG) di SMK N 1 Singkarak - Afdilatun Nisa; Indra Wijaya; Rini Sefriani (CV Putra Publisher, 2023)
This study aims to determine the level of validity, practicality, and effectiveness of the Development Of Project Based Learning (PjBL) Learning E-Modules Using Sigil In The Subjects Of Vocational Basics Of Students In Class X Software And Game Development (PPLG) At SMK 1 Singkarak Even Semester Year Teaching 2022/2023. This study uses the development model (ADDIE) with the following development steps: (1) Analyze, (2) Design, (3) Development, (4) Implementation and (5) Evalurate. The research subjects number of 31 people. The whole research on validator test On E-Modules Uses Sigil In The Basic Subjects Of Vocational Class X PPLG At SMKN 1 Singkarak by 92.73%, with very valid interpretation used. The research subjects number of 31 people. Overall practicality test research on E-Modules Using Sigil In The Basic Subjects Of Vocational Class X PPLG At SMKN 1 Singkarak by 93.81%, with very practical interpretation of use. The results of the overall effectiveness test of the effectiveness of the effectiveness of E-Modules Using Sigil In The Basic Subjects Of Vocational Class X PPLG In SMKN 1 Singkarak 89.29% are very effective. In the subjects of vocational basics, students of class X Software and Game Development (PPLG) at SMKN 1 Singkarak have been tested for feasibility, excellence, and can be used in learning activities in the subjects of vocational basics in class X PPLG in SMKN 1 Singkarak.